2019
DOI: 10.1177/1938640019826692
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Metabolic Syndrome on 30-Day Outcomes Following ORIF for Ankle Fractures

Abstract: Introduction: Metabolic syndrome (MetS) is associated with significant postoperative morbidity. Despite an increasing prevalence of MetS in the US population, its impact on postoperative outcomes following ankle fractures remains limited. Materials and Methods: The 2012-2016 American College of Surgeons–National Surgical Quality Improvement Program database was queried for patients undergoing open reduction with internal fixation (ORIF) for ankle fractures using Current Procedural Terminology codes: 27766, 277… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Patients with MetS had a 9.1% readmission rate after discharge compared to a 3.7% readmission rate in non-MetS patients (OR 2.62). Our data reaffirm findings from recent literature that show MetS to be a risk factor for increasing 30-day readmission rate after ankle fracture [ 8 ]. These findings further establish that patients with MetS require careful perioperative management to reduce readmission.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Patients with MetS had a 9.1% readmission rate after discharge compared to a 3.7% readmission rate in non-MetS patients (OR 2.62). Our data reaffirm findings from recent literature that show MetS to be a risk factor for increasing 30-day readmission rate after ankle fracture [ 8 ]. These findings further establish that patients with MetS require careful perioperative management to reduce readmission.…”
Section: Discussionsupporting
confidence: 92%
“…The Xie et al. study, which analyzed the impact of MetS on post-operative outcomes after ankle fracture, observed differences that approached statistical significance (p = .054), but ultimately fell short [ 8 ]. Conversely, Cheng et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Included Studies). Most studies reported North America data ( n =40) 4 6 , 15 , 23 , 27 , 30 35 , 38 40 , 43 , 46 49 , 52 , 53 , 55 62 , 65 67 , 70 , 73 , 75 78 , 80 , with the remaining spanning Europe 19 , 21 , 22 , 24 , 28 , 42 , 44 , 50 , 51 , 64 , 68 , 81 , the Middle East 20 , Asia 37 , 41 , 45 , 71 , 72 , 74 , 82 , 83 , Africa 63 , and South America 54 . The assessed risk of bias of the included studies ranged from 5 to 8 (fair to good) out of a possible 9 stars when assessed using the NOS.…”
Section: Resultsmentioning
confidence: 99%
“…This database is a risk-adjusted, outcome-based quality improvement program whose goal is for the improvement of surgical outcomes. All data are validated by trained reviewers through the use of medical records, patient interviews, and operative reports, with a very low disagreement rate [ 12 ]. Variables collected include preoperative, intraoperative, and postoperative data [ 13 ].…”
Section: Methodsmentioning
confidence: 99%